What do gay men want? : an essay on sex, risk, and subjectivity - Halperin, David M., 1952- (University of Michigan Press, 2007)
"Recent efforts to analyze gay men's motives for sexual risk-taking in the context of the HIV/AIDS epidemic have led to a revival of medical thinking about homosexuality and breathed new life into punitive cliches about gay men's alleged low self-esteem, lack of self-control and various psychological "deficits." Against these insidious forms of sexual discipline, David Halperin champions neglected traditions of queer thought, both literary and popular, that afford possibilities for addressing the vexed question of what gay men want. Anyone searching for creative and non-judgmental ways to slow the spread of HIV/AIDS among gay men - or interested in new modes of thinking about gay male subjectivity - should read this book."--Jacket